Efficient isolation of pure and functional mitochondria from mouse tissues using automated tissue disruption and enrichment with anti-TOM22 magnetic beads. - Andras Franko (PLoS ONE, 2013)
To better understand molecular mechanisms regulating changes in metabolism, as observed e.g. in diabetes or neuronal disorders, the function of mitochondria needs to be precisely determined. The usual isolation methods such as differential centrifugation result in isolates of highly variable quality and quantity. To fulfill the need of a reproducible isolation method from solid tissues, which is suitable to handle parallel samples simultaneously, we developed a protocol based on anti-TOM22 (translocase of outer mitochondrial membrane 22 homolog) antibody-coupled magnetic beads. To measure oxygen consumption rate in isolated mitochondria from various mouse tissues, a traditional Clark electrode and the high-throughput XF Extracellular Flux Analyzer were used. Furthermore, Western blots, transmission electron microscopic and proteomic studies were performed to analyze the purity and integrity of the mitochondrial preparations. Mitochondrial fractions isolated from liver, brain and skeletal muscle by anti-TOM22 magnetic beads showed oxygen consumption capacities comparable to previously reported values and little contamination with other organelles. The purity and quality of isolated mitochondria using anti-TOM22 magnetic beads was compared to traditional differential centrifugation protocol in liver and the results indicated an obvious advantage of the magnetic beads method compared to the traditional differential centrifugation technique.